Interaction effects between Paraoxonase 1 variants and cigarette smoking on risk of coronary heart disease in a Singaporean Chinese population. Issue 1 (May 2015) - Han, Yi; Dorajoo, Rajkumar; Ke, Tingjing; Ayala, Burger; Chang, Xuling; Khor, Chiea-Chuen; van Dam, Rob M.; Yuan, Jian-Min; Koh, Woon-Puay; Liu, Jianjun; Goh, Daniel Y.T.; Friedlander, Yechiel; et al.
Abstract Objective Paraoxonase 1 (PON1) plays an important role in reducing the risk of coronary heart disease (CHD). Smoking is known to reduce PON1 activity. We aimed to investigate the effects of interactions between PON1 variants and smoking on CHD in the Singaporean Chinese population. Methods In a case-control study nested within Singapore Chinese Health Study (N = 1914), subjects with and without CHD were classified into never-smokers and ever-smokers (ever smoked at least one cigarette a day for 1 year or longer). Associations at four independent SNPs at the PON1 locus (rs3735590, rs3917550, rs662, rs3917481) with CHD were evaluated using logistic regression, before/after stratification on smoking status. Interactions between smoking and PON1 variants were analyzed with likelihood ratio tests, by including the SNP*smoking interaction term in regression analyses. Results The T allele at the coding SNP, rs662, was associated with higher risk of CHD in ever-smokers only (OR = 1.35, 95% CI 1.08–1.68; adjusted P = 0.036). At the miR-SNP, rs3735590, carrying at least one copy of minor allele T was associated with increased risk of CHD in a dominant manner in never-smokers only (OR = 1.53, 95% CI 1.11–2.11; adjusted P = 0.036). Significant interactions between two PON1 SNPs and smoking in relation to CHD risk were identified (adjusted P = 0.012 for rs662; adjusted P = 0.044 for rs3735590). These associations remained significant after adjustment for known CHD risk factors and upon correction for multiple tests. Conclusions Two PON1 SNPs, rs662 and rs3735590, were found to significantly interact with cigarette smoking to modulate the risk of CHD in the Singaporean Chinese population.